The free radical scavenging and cytotoxic properties of Ardisia crenata and Peliosanthes teta in the 4T1 breast cancer cell line - Yassir Mohammed Ali Al-Zubaidi; Arifah Abdul Kadir; Zainul Amiruddin Zakaria (Al-Rafidain University College, 2024)
Background: Ardisia crenata (A. crenata) and Peliosanthes teta Andrew (P. teta) are popular medicinal plants in Malaysia that are claimed to have several biological effects. Objective: To assess the anticancer and radical-scavenging properties of A. crenata and P. teta methanolic extracts. Methods: TPC was quantified using the Folin-Ciocalteu test; free radical scavenging was evaluated using the 2,2'-azino-bis3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays; and cytotoxic activity was assessed using the MTT assay. Results: In both ABTS and DPPH systems, A. crenata exhibits much higher radical scavenging activity than ascorbic acid. P. teta showed less significant antioxidant activity. Furthermore, A. crenata methanolic extracts demonstrated free radical scavenging properties in a concentration-dependent manner, quenching ABTS and DPPH radicals with no lag phase observed in the experiments. Furthermore, A. crenata had a strong cytotoxic effect on the breast cancer 4T1 cell line but had no suppression of cell viability in the 3T3 normal fibroblast cell line. Interestingly, the TPC of A. crenata was significantly higher than that of P. teta methanolic extracts. Conclusions: A. crenata showed antioxidant and anticancer action against breast cancer 4T1 cells, indicating that it could be a valuable source for future pharmacological and medical research.